Fat oxidation in men and women endurance athletes in running and cycling - Knechtle, B.; Müller, G.; Willmann, F.; Kotteck, K.; Eser, P.; Knecht, H. (International Journal of Sports Medicine, 2004)
Recent studies showed that the maximal fat oxidation seems to be different in men and women and that it can be influenced by type and intensity of exercise. Nineteen endurance trained male (V.O (2)peak 61.3 +/- 4.4 ml x kg (-1) x min (-1)) and 17 female (V.O (2)peak 52.8 +/- 4.5 ml x kg (-1) x min (-1)) athletes were studied over 30 min at 55, 65 and 75 % V.O (2)peak on a treadmill and a cycling ergometer in order to find the intensity and kind of exercise with the highest absolute fat oxidation. For women, normalised (per body weight) fat oxidation was higher at 75 % V.O (2)peak than at 55 % V.O (2)peak for both running (p = 0.02) and cycling (p = 0.01). Women also oxidised a significantly higher percentage of fat with regard to total energy expenditure than men in running (p = 0.02) and cycling (p = 0.004). Normalised carbohydrate oxidation was significantly higher for men at each tested intensity (p < 0.05) and compared to kind of exercise in men (p = 0.006) and women (p = 0.002) in cycling than in running. Men and women showed a significantly higher normalised fat oxidation for running compared to cycling (p = 0.01). Cycling produced in men (p = 0.06) and women (p = 0.001) significantly more lactate than running. In summary, we found at 75 % V.O (2)peak a higher fat oxidation rate than at 65 % V.O (2)peak and 55 % V.O (2)peak for men and women in cycling and running. This is coincident with lactate threshold in men and women in cycling but not in running, where lactate threshold is higher than 75 % V.O (2)peak.